(untitled) (Applied Biological Research, 2022)
Leukemia is the most diagnosed form of cancer that attacks adults and children. It is a heterogeneous group of acquired clonal hematological malignancies that incorporates diverse biologically distinct subgroups. The aim of present study was to assess the distribution of different blood groups in acute leukemia patients of Kurdish Iraq’s. This retrospective descriptive study was conducted on 533 patients who visited Hiwa Cancer Hospital, Sulaymaniyah, Kurdistan region, Iraq from January 2015 to December 2020. The age, gender, and leukemia type along ABO blood groups were determined. Overall, 533 acute leukemia patients, including acute lymphatic eukemia (ALL) and acute myeloblastic leukemia (AML), were diagnosed. There were 316 male and 217 female patients (ratio 1.46:1), with the age range >1 to 102 years. The study showed that in 5.6% patients none of the blood types were registered. Similarly, the ABO blood group distributions were 186 (34.9%) O, 156 (29.3%) A, 131 (24.6%) B, and 30 (5.6%) AB. All the groups A, AB, and O were positively and significantly related to acute leukemia. From beta coefficient value O group was found more vulnerable to ALL and AML at 0.444 and 0.445, respectively.